2020
DOI: 10.3390/catal10101164
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Transition Metal Carbide Electrocatalysts for Oxygen Evolution Reaction

Abstract: The electrolysis of water is considered to be a primary method for the mass production of hydrogen on a large scale, as a substitute for unsustainable fossil fuels in the future. However, it is highly restricted by the sluggish kinetics of the four-electron process of the oxygen evolution reaction (OER). Therefore, there is quite an urgent need to develop efficient, abundant, and economical electrocatalysts. Transition metal carbides (TMCs) have recently been recognized as promising electrocatalysts for OER du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 118 publications
(140 reference statements)
0
26
0
Order By: Relevance
“…Recently, researchers found that metal carbides, specifically transitional metal carbides, can be applied as electrocatalysts for OER owing to their high stability. 215 Some doped metal carbides and their performances are listed in Table 4. The activity of TM carbides was improved by including one or more foreign dopants into their lattice domain.…”
Section: Metal Nitrides and Carbidesmentioning
confidence: 99%
“…Recently, researchers found that metal carbides, specifically transitional metal carbides, can be applied as electrocatalysts for OER owing to their high stability. 215 Some doped metal carbides and their performances are listed in Table 4. The activity of TM carbides was improved by including one or more foreign dopants into their lattice domain.…”
Section: Metal Nitrides and Carbidesmentioning
confidence: 99%
“…P. Cai et al [12] have introduced amorphous cobalt sulphide nanocubes as an OER electrocatalyst. Y. Wang et al [13] have given insights into the myriads of metal carbides for OER activities. Moreover, carbon nanostructured materials have also been exploited for efficient OER as a metal-free electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid resource constraints and reduce costs, catalytic materials that do not use heavy or precious metals such as Pt are needed [ 6 ]. The OER occurring at the cathode of rechargeable metal–air batteries and at the anode of water electrolysis systems [ 7 ] is also an important process for efficient O 2 generation in such devices [ 8 ]. Pt, Ir, Ru, and other precious-metal catalysts have been used to reduce the OER overpotential, which is associated with the bottleneck process in water electrolysis.…”
Section: Introductionmentioning
confidence: 99%